(untitled) (Anales de la Real Academia de Medicina y Cirugía de Valladolid, 2024)
The best way to learn about language is through the analysis of speech samples that human beings show in their oral interactions. In Aging and language. Corpus of speech samples of people with mild cognitive impairment in structured interviews, the authors gather in a corpus of oral interviews the speech samples recorded, and subsequently transcribed, in social-health centres of the population over 65 years of age, a few months before the COVID-19 pandemic. Based on the analysis of their discourse, from corpus linguistics and conversational pragmatics, an empirical source of speech samples obtained in semi-structured interviews between a speech therapist and an elderly person with mild or moderate cognitive impairment is offered to speech therapy professionals, researchers and relatives of people with language impairment due to neurocognitive impairment. Through the analysis of the linguistic characteristics and psychopathological manifestations of the people interviewed, speech therapists and interested professionals will have at their disposal a set of speech samples with which to contribute to improving the care and quality of life of the elderly, as well as an aid for the creation of specific intervention programmes for the communication of our elders.